2022
DOI: 10.1021/acs.est.1c06126
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Fate of Cl-PFPECAs: Predicting the Formation of PFAS Transformation Products in New Jersey Soils

Abstract: Although next-generation per- and polyfluorinated substances (PFAS) were designed and implemented as safer and environmentally degradable alternatives to “forever” legacy PFAS, there is little evidence to support the actual transformation of these compounds and less evidence of the safety of transformed products in the environment. Multiple congeners of one such PFAS alternative, the chloro-perfluoropolyether carboxylates (Cl-PFPECAs), have been found in New Jersey soils surrounding a manufacturing facility. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
(85 reference statements)
1
10
0
Order By: Relevance
“…In contrast, non-targeted analysis includes methods that detect known and unknown analytes. Typically, high-resolution mass spectrometry (HRMS) is used for non-targeted analysis, as employed by [92] to predict the fate of new generations of PFAS. These instruments are capable of measuring both known and unknown analytes, and data can be stored in HRMS for analyzing new analytes later.…”
Section: Analytical Methods For the Detection And Quantification Of Pfasmentioning
confidence: 99%
“…In contrast, non-targeted analysis includes methods that detect known and unknown analytes. Typically, high-resolution mass spectrometry (HRMS) is used for non-targeted analysis, as employed by [92] to predict the fate of new generations of PFAS. These instruments are capable of measuring both known and unknown analytes, and data can be stored in HRMS for analyzing new analytes later.…”
Section: Analytical Methods For the Detection And Quantification Of Pfasmentioning
confidence: 99%
“…Besides that, based on the newly identified PFAS alternative, chloroperfluoropolyether carboxylates (Cl‐PFPECAs) reported by Washington et al. in Science , 58 a further investigation using qTOF HR MS‐based non‐targeted screening and literature reports‐based TPs prediction was conducted 59 . According to the generated transformative structures and screening results obtained from the NTA of HR LC‐MS/MS, a series of Cl‐PFPECAs TPs and their congeners with different functional groups, that is, hydroxy‐, vinyl‐, expo‐, and dihydroxy‐ substituted Cl‐PFPECAs were tentatively observed as the proposed PFAS transformation schemes demonstrated (Figure 4B).…”
Section: Recent Progress In the Analysis Of Pm25‐bonded Transformatio...mentioning
confidence: 99%
“…Major manufacturers of per- and polyfluoroalkyl substances (PFAS) have phased out the production of perfluorooctanoic acid (PFOA), perfluorooctanesulfonic acid (PFOS), and related substances , due to public concern about their persistence, toxicity, , and ubiquitous presence in the environment. Perfluoroalkyl ether carboxylic acids (PFECAs) and short-chain perfluoroalkyl carboxylic acids (PFCAs) have been introduced into the market to replace PFOA and PFOS. However, these replacement substances are also recalcitrant to degradation , and environmentally mobile. , PFECAs and short-chain PFCAs, including hexafluoropropylene oxide dimer acid (HFPO-DA), perfluorobutanoic acid (PFBA, C4), and perfluoropentanoic acid (PFPeA, C5), have been frequently detected in surface and groundwater worldwide. ,, Hexafluoropropylene oxide trimer acid (HFPO-TA), a novel alternative to PFOA, has recently been observed in surface water. , Acute and long-term toxicological studies have revealed the hazardous properties of HFPO-DA, HFPO-TA, and short-chain PFCAs. The U.S. Environmental Protection Agency (EPA) has recently issued the final health advisory for HFPO-DA and its ammonium salt (“GenX” chemicals) in drinking water at 10 ng/L . In the European Union, the recently updated Drinking Water Directive recommends limits of 100 ng/L for 20 PFAS, including PFBA and PFPeA .…”
Section: Introductionmentioning
confidence: 99%